Case report: Continuous spinal cord physiologic monitoring following traumatic spinal cord injury—A report from the Winnipeg Intraspinal Pressure Study (WISP) - Dhaliwal, Perry; Gomez, Alwyn; Zeiler, Frederick Adam (Frontiers in Neurology, 2023)
Introduction Acute traumatic spinal cord injury is routinely managed by surgical decompression and instrumentation of the spine. Guidelines also suggest elevating mean arterial pressure to 85 mmHg to mitigate secondary injury. However, the evidence for these recommendations remains very limited. There is now considerable interest in measuring spinal cord perfusion pressure by monitoring mean arterial pressure and intraspinal pressure. Here, we present our first institutional experience of using a strain gauge pressure transducer monitor to measure intraspinal pressure and subsequent derivation of spinal cord perfusion pressure. Case presentation The patient presented to medical attention after a fall off of scaffolding. A trauma assessment was completed at a local emergency room. He did not have any motor strength or sensation to the lower extremities. A computed tomography (CT) scan of the thoracolumbar spine confirmed a T12 burst fracture with retropulsion of bone fragments into the spinal canal. He was taken to surgery for urgent decompression of the spinal cord and instrumentation of the spine. A subdural strain gauge pressure monitor was placed at the site of injury through a small dural incision. Mean arterial pressure and intraspinal pressure were then monitored for 5 days after surgery. Spinal cord perfusion pressure was derived. The procedure was performed without complication and the patient underwent rehabilitation for 3 months where he regained some motor and sensory function in his lower extremities. Conclusion The first North American attempt at insertion of a strain gauge pressure monitor into the subdural space at the site of injury following acute traumatic spinal cord injury was performed successfully and without complication. Spinal cord perfusion pressure was derived successfully using this physiological monitoring. Further research efforts to validate this technique are required.